WORKSHOP PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT BERDESAIN LINGKUNGAN SISWA BAGI GURU SD - Putri Yuanita; Elfis Suanto; Nahor Murani Hutapea; Rini Dian Anggraini; Susda Heleni; Suci Andriani; Sehatta Saragih (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Paying attention to the intellectual development of elementary school students in the lower classes and the demands of the implementation of deep learning, bringing the context of the student environment into learning is a must. One of the efforts that can be made is through the use of ICT-based learning media with student environmental design. However, the limited ability of teachers to develop the media is an obstacle, so mentoring activities are needed. This community service activity aims to improve teachers' ability to develop ICT-based learning media with student environmental design through workshops. The activity was carried out in collaboration with the Siak Regency Education Office with a target of 51 grade I teachers in Kandis District. The workshop was held for four sessions at SDN 09 Kandis using presentation, discussion, practice, and simulation methods. Indicators of the success of the activities are measured through the ability of participants to produce media products and responses to the implementation of the activities. The results of the activity showed that participants were able to produce ICT-based learning media designed by students with a good category. In addition, the participants' response to the activity was very positive, where all participants stated that the activity helped them in developing learning media. The enthusiasm of the participants and the basic ability to use ICT are the supporting factors for the success of the activity, while the main obstacle lies in the ability to compile the structure of the material as well as in browsing, downloading and cutting the media context. This workshop activity was declared effective in improving teachers' abilities and experience in developing ICT-based learning media that is contextual and in accordance with the characteristics of elementary school students.